L’affaire Belmoral - Cyr, Caroline (Criminologie, 1988)
This note reports on the various causes underlying the collapse of the Belmoral Mine in Val d'Or, Québec, in May 1980. It relays the facts concerning the events preceding and following this tragedy: reports on the working conditions, the public inquest and its conclusions, and the court hearings. Based on information drawn from these sources and from the press, the author reconstructs the events surrounding the tragedy and the arguments presented by Belmoral management and independent experts, denying or supporting the theory that the collapse of the mine was foreseeable and therefore preventable. The object of this paper is to state the facts, as objectively as possible, allowing the readers to draw their own conclusions concerning this matter.